2021
DOI: 10.1016/j.annonc.2021.08.1591
|View full text |Cite
|
Sign up to set email alerts
|

1598P Acceptance of SARS-CoV-2 vaccination among patients with cancer undergoing immunosuppressive therapy: Portuguese study

Abstract: Background: Cancer p represent a high-risk population for severe COVID-19. Cancerassociated immunosuppression may hinder in the development of anti-SARS-CoV-2 antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Similar results have been documented in a Portuguese study by de Sousa et al where a majority of cancer patients (84%) on immunosuppressive therapy had the intention to be vaccinated, as well as a Lebanese study where 55% of patients had shown willingness for COVID-19 vaccination [ 46 ].…”
Section: Discussionsupporting
confidence: 86%
“…Similar results have been documented in a Portuguese study by de Sousa et al where a majority of cancer patients (84%) on immunosuppressive therapy had the intention to be vaccinated, as well as a Lebanese study where 55% of patients had shown willingness for COVID-19 vaccination [ 46 ].…”
Section: Discussionsupporting
confidence: 86%
“…This vaccination rate is higher than the global and European Union rates (46.3% and 68.1%, respectively) [40]. In a study conducted among Portuguese immunosuppressed cancer patients three months after implementing the vaccination program, the vaccine acceptance was 84.0% [39]. However, in a prior cross-sectional analysis of the Portuguese communitybased survey "COVID-19 Barometer: Social Opinion" using data from 29 September 2020 to 8 January 2021, only 35.3% of the individuals would like to be vaccinated as soon as possible, with most (55.5%) preferring to wait some time before being vaccinated and 9.2% refusing the vaccination [38].…”
Section: Introductionmentioning
confidence: 96%